2016
DOI: 10.1186/s40064-016-2158-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surface water quality indices and ecological risk assessment for heavy metals in scrap yard neighbourhood

Abstract: Pollution of surface water with heavy metals from industrial activities especially those from scrap yard has caused a major threat to human life exposing man to series of hazard, diseases, disability and consequently death. This study focuses on water quality indices of Owode-Onirin and Lafenwa scrap yard with respect to its physicochemical parameters and heavy metal concentrations by evaluating Heavy Metal Pollution Index (HPI), Metal Index (MI) and Potential Ecological Risk Index (PERI). Fifteen water sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(50 citation statements)
references
References 27 publications
3
45
2
Order By: Relevance
“…Anthropogenic impacts on the study environment are other factor traceable to the elevated level of their radionuclides. Groundwater pollution of the study area arising from point and non-point sources has been reported in literature (Ojekunle et al, 2016;Adekunle et al, 2013;Olurin et al, 2012).…”
Section: Discussion On Activity Concentrations Of the Water Samplesmentioning
confidence: 99%
“…Anthropogenic impacts on the study environment are other factor traceable to the elevated level of their radionuclides. Groundwater pollution of the study area arising from point and non-point sources has been reported in literature (Ojekunle et al, 2016;Adekunle et al, 2013;Olurin et al, 2012).…”
Section: Discussion On Activity Concentrations Of the Water Samplesmentioning
confidence: 99%
“…HPI of a river can be a useful tool for regulatory agencies to make necessary policies and decisions regarding pollution abatement and resource management. The metal quality indices have been computed to assess the suitability level of water resources for drinking with respect to metals (Ojekunle et al, 2016). Pearson's correlation analysis can be an effective tool for identification of pollution sources, to apportion natural versus anthropogenic or mixed contributions (Yalcin et al, 2010;Manoj et al, 2012).…”
Section: Issn: 2319-7706 Volume 6 Number 12 (2017) Pp 1491-1498mentioning
confidence: 99%
“…In this study the observation of the heavy metals showed high concentration of Manganese (Mn), Arsenic (As) and Cadmium (Cd) than the maximum permissible limit need to be present in drinking water according to the WHO guidelines of water [7].…”
Section: Concentration Of Heavy Metalsmentioning
confidence: 85%
“…Untreated or purportedly treated industrial effluents and sewage water contain variable amounts of heavy metals, for example, arsenic, lead, nickel, cadmium, copper, mercury, zinc, and chromium [6] which is broadly studied and their consequences for human wellbeing are routinely evaluated by international bodies such as the WHO. In the result of trace metals, the permissible limit of the content of arsenic, lead and manganese in the surface water samples was found to be <0.05 mg/L whereas the WHO permissible limit of cadmium is 0.005 mg/L [7].…”
Section: Introductionmentioning
confidence: 90%